2021
DOI: 10.1093/nar/gkaa1236
|View full text |Cite
|
Sign up to set email alerts
|

Precise and broad scope genome editing based on high-specificity Cas9 nickases

Abstract: RNA-guided nucleases (RGNs) based on CRISPR systems permit installing short and large edits within eukaryotic genomes. However, precise genome editing is often hindered due to nuclease off-target activities and the multiple-copy character of the vast majority of chromosomal sequences. Dual nicking RGNs and high-specificity RGNs both exhibit low off-target activities. Here, we report that high-specificity Cas9 nucleases are convertible into nicking Cas9D10A variants whose precision is superior to that of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…These methods work with substantially less Cas9 dependent off-targets than nucleases, nevertheless, they also rely on cleavage, i.e., the nickase activity of SpCas9. The nickase versions of IFNs seem to exhibit the same sensitivity to the sequence contributions of the targets 32, 68 , thus applying target-matched IFN base and prime editors may decrease off-target editing of current editors to a non-detectable level and further. (vii) The identification of target-matched IFNs for a given target has proved to be straightforward here, still, a predictive algorithm, which could identify the target-matched IFNs for specific targets could further simplify this process and make it less labour intensive.…”
Section: Discussionmentioning
confidence: 99%
“…These methods work with substantially less Cas9 dependent off-targets than nucleases, nevertheless, they also rely on cleavage, i.e., the nickase activity of SpCas9. The nickase versions of IFNs seem to exhibit the same sensitivity to the sequence contributions of the targets 32, 68 , thus applying target-matched IFN base and prime editors may decrease off-target editing of current editors to a non-detectable level and further. (vii) The identification of target-matched IFNs for a given target has proved to be straightforward here, still, a predictive algorithm, which could identify the target-matched IFNs for specific targets could further simplify this process and make it less labour intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, this approach has not yet been explored and used for the Cas9 protein structural diversity to identify good adaptive routes to higher fitness ( Gao et al, 2020 ). Concomitant with that, the need of multiple mutated residues in Cas9 has been predicted to improve specificity and efficiency by changing the conformational dynamics and biophysical properties of the iCas9 at different stages of its activity ( Palermo et al, 2017 , 2018 ; Boyle et al, 2021 ; Wang et al, 2021 ). Mostly, these residues mediate the allosteric communication of Cas9 (i.e., flexibility of the three conformational stages) and the RNA/DNA heteroduplex to ensure the proper positioning of the catalytic site and the proofreading step ( Yang et al, 2018 ).…”
Section: The Crispr/cas9 Systemmentioning
confidence: 99%
“…69 It has been reported that the use of the inactivated RuvC domain of Cas-9 with sgRNA can reduce the off-target effect by 100 to 1500 times. 70 Moreover, the nuclease Cas-12a (previously known as Cpf1) is a type V CRISPR/Cas system that provides high genome editing efficiency. 71 Unlike the CRISPR/Cas-9 system, CRISPR/Cas-12a can process pre-crRNA into mature crRNA without tracrRNA, thereby reducing the size of plasmid constructs.…”
Section: Challenges For Crispr/cas-9 Applicationmentioning
confidence: 99%